LINGUISTIC DIFFERENCES BETWEEN BRITISH AND AMERICAN ENGLISH - Ibayev Anvar Jurabekovich,; Aktamova Dilnoza Bozorboy qizi,; Zokirova Sevinch Quvonchbek qizi,; Beknazarova Dinara Matlubjon qizi,; Boliqulova Muxlisa Nomoz qizi,; Ismatullayeva Bahora G'aybulla qizi, (TADQIQOTLAR, 2026)
Abstract: This article investigates the primary linguistic distinctions between British  English  and  American  English,  concentrating  on  phonetic,  lexical, grammatical, orthographic, and pragmatic dimensions. Both varieties come from the same  historical  source,  but  they  have  grown  apart  because  of  where  they  are,  the cultures they are in, and how they have evolved as languages. The research underscores variations in pronunciation, including rhotic and non-rhotic accents; discrepancies in vocabulary,  encompassing  everyday  lexical  items;  distinctions  in  spelling;  and grammatical  preferences  regarding  tense  usage,  prepositions,  and  collective  nouns. There is also a focus on stylistic and pragmatic subtleties that affect communication in academic, professional, and casual settings. By examining these distinctions, the study illustrates that British and American English constitute standardized national varieties within  a  singular  language  system  rather  than  distinct  languages.  To  communicate effectively  across  cultures,  teach  languages,  study  translation,  and  do  linguistic research, you need to know about these differences. The results add to comparative linguistics by giving a systematic overview of the structural and functional differences between the two main types of English.